The Influence of “Search Engine” Utilization Toward English Master Students’ Learning Culture - Gayo, Isnawi (STKIP Yapis Dompu, 2022)
Search engines are tools to seek, identify and retrieve information on different websites. In this modern era, the changes of learning culture among higher education students are undeniable, especially on the use of internet. This paper aims to investigate the effectiveness of search engine utilization toward learning culture of English Master students of Universitas Ahmad Dahlan. The Participants were 10 students which consist of five males and five females. This research was under qualitative research followed by direct observation through semi-structured interview. Based on data interview, it showed that the participants are enthusiasm in using search engine. The result presents that search engine utilization has positive effects in enhancing students’ knowledge in the learning culture development. Furthermore, the utilization of search engine in improving the positive learning culture should be continued with different styles of educational approaches in the future.